Automation of the unit for regeneration of ionic filters for chemical desalination of water - Khayrulla S. Isoxodjayev; Zohid Y. Hasanov; Siroj K. Yarashov (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: in this article, an automatic control system for the regeneration unit of ionic exchange filters during chemical desalination of water has been developed. the regeneration unit for ion exchange filters during chemical desalination of water was automated. Based on the algorithm, a functional diagram of the logic control system was developed, and the maximum throughput of the KPRS 600 valve was determined to establish the control range. Aim: automation of the system for regenerating ionic exchange filters used in water desalination based on chemical reagents Methods: differential discretization derived from conservation of mass and energy in the channels was used using the finite difference method. Results: the effectiveness of the proposed chemical reagent-based water desalination was evaluated on a monthly basis for five cities in Uzbekistan (Karshi and Termez with hot-dry climates, and Tashkent, Andijan, Namangan, and Fergana with hot-humid climates). During this work, the regeneration unit for ionic exchange filters used in chemical water desalination was automated. Based on the developed algorithm, a functional diagram of the control system was created, and the maximum flow capacity of the KPRS 600 valve was determined to establish the control range.